Ảnh hưởng của ion đối pha tạp đến khả năng bảo vệ chống ăn mòn của lớp phủ epoxy chứa polypyrol dẫn điện - Lê Hiền và cộng sự, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The conducting polypyrrole doped by thee different dopant (dodecylbenzensulfonic acid, aminotrimethylene phosphonic acid and molydate) was prepared by chemical oxidative method using ammoniumpersulphate. The polymer obtained was characterized by SEM, TEM and Raman spectra. The polymer was dispersed in epoxi resin and the corrosion protection property of the coating for steel has been evaluated by open circuit potential measurements and EIS. The result of corrosion test showed that Ppy had a posibility of adherence improvement of the epoxi coating and can self-heal by supply of its positive charge and couter-ions dopant at corrosion metal possitions. So the epoxi coating in the presence of Ppy had protection time more durable than the coating without Ppy.